From independence to interdependence : Iceland's return connectedness after financial liberalization and frontier classification. A TVP-VAR approach - Kári Hallsteinsson 1993- (2022)
This study analyzes the connectedness of returns between five Nordic stock markets, Germany, the United Kingdom, and the United States. The key focus of this study is how Iceland’s financial liberalization and subsequent frontier market classification affected Iceland’s connectedness to the other examined markets. The whole sample, ranging from March 2012 to July 2022, is split into three subperiods, reflecting Iceland’s capital controls (March 2012 to June 2015), their lifting (June 2015 to September 2019), and Iceland’s frontier classification (September 2019 to July 2022). The static and dynamic measures used in the analysis were estimated with an approach based on time-varying parameter vector autoregressions (TVP-VAR). The analysis of the static measures shows that Iceland’s return variations are largely explained endogenously during the capital controls and after they were lifted. However, after the frontier classification, Iceland became highly interconnected and received similar levels of spillovers as Denmark and the United States. The dynamic measures reveal a gradual increase in Iceland’s connectedness following Iceland’s financial liberalization. In addition, after COVID-19, the interconnectedness of the examined markets increases considerably. The total directional measures reveal that the connectedness of the examined markets has, for the most part, gone to pre-pandemic levels. However, Iceland has remained highly connected. Furthermore, Iceland is primarily a net recipient of spillovers, mainly from Finland, Sweden, and Germany after the pandemic. The frontier classification has shifted Iceland from the independence of shocks towards interdependence, but how much of this change is attributable to COVID-19, or the frontier classification, remains unclear.